Mevalonic aciduria: Does stem cell transplant fully cure disease?. (25th October 2019) - Szymanski, Ann Marie; Dávila Saldaña, Blachy; Ferreira, Carlos R.; Loechelt, Brett; Jung, Lawrence
Abstract: MA is a rare, autosomal recessive disorder characterized by episodes of inflammation and periodic fevers. In its most severe form, it can result in facial dysmorphism, growth inhibition, ataxia, liver dysfunction, intellectual disability, and at times can be fatal. A number of case reports exist stating that SCT is curative in these patients. We present the case of a patient diagnosed with MA at birth, who underwent SCT at the age of 14 months with intent to cure. She achieved complete engraftment and urine mevalonate became undetectable. However, 18 months following transplant, she developed frequent episodes of fevers, rashes, arthritis, and a rising urinary mevalonate. She was subsequently diagnosed with relapse. She now requires treatment with steroids and canakinumab to manage her disease. This case is the first report of disease relapse following transplant for MA. It runs contrary to prior reports that SCT is fully curative of MA and suggests that transplant may instead provide a means of decreasing disease severity without entirely eradicating the condition.